1 / 9

Section 2.2 Induction Proof by induction: to prove p(n) true,  n

Section 2.2 Induction Proof by induction: to prove p(n) true,  n Idea: like playing the domino game. Suppose dominos are placed correctly, then hitting the 1 st domino, when it falls, we know the rest of them will also fall.

ltommie
Download Presentation

Section 2.2 Induction Proof by induction: to prove p(n) true,  n

An Image/Link below is provided (as is) to download presentation Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author. Content is provided to you AS IS for your information and personal use only. Download presentation by click this link. While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server. During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

Presentation Transcript


  1. Section 2.2 Induction Proof by induction:to prove p(n) true, n Idea: like playing the domino game. Suppose dominos are placed correctly, then hitting the 1st domino, when it falls, we know the rest of them will also fall. ( the 2nd will fall, in general, when the kth one falls, it implies the (k+1)th falls. Since k is any arbitrary number, actually every domino falls.)

  2. Induction: Step1: (inductive base) or IB is to show that p(1) true Step2: (inductive step) or IS is to show that p(k)  p(k + 1), where p(k) is called inductive hypothesis or IH.

  3. e.g. show 1+3+5+…(2n-1) = n2, n  1 IB: when n = 1, LHS = 1 = 12 = RHS IS: Assume 1+3+5+….(2k-1)=k2 and want to Show 1+3+5+…(2k-1) + [ 2(k+1)-1] =(k+1)2 1+3+5+…(2k –1) + (2k + 1) = k2 + 2k+ 1 = (k +1)2 k2 (by IH)

  4. n(n+1) 2 e.g. Show 1 + 2 + 3 + … n = ,  n  1 IB: when n = 1, LHS = 1 = = RHS IS: Assume 1 + 2 + 3 + …k = and want to show 1 + 2 + 3 + …+ k + (k+1) = 1(1+1) 2 k(k+1) 2 (k+1)(k+2) 2

  5. k(k+1) 2 1 + 2 + 3 + …+ k + (k+1) = + (k+1) = = by direct proof: Let x = 1 + 2 + 3 + …+ k +) x = k + k-1 + k-2 + … + 1 2x = (k+1)+(k+1)+ … +(k+1)  x = k(k+1) 2 (by IH) k(k+1) + 2(k+1) 2 (k+1) (k+2) 2 k of them k(k+1) 2

  6. eg: Show 1+ 21+ 22 + … + 2n = 2n+1 – 1,  n  IB: when n = 1, LHS = 1+ 2 = 22 - 1 = RHS IS: Assume 1 + 2 + 22 + … 2k = 2k+1 – 1, and Show 1 + 2 + 22 + … 2k + 2k+1 = 2k+2 – 1  1 + 2 + 22 + … 2k + 2k+1 = 2k+1 – 1 + 2k+1 = 2*2k+1 – 1 = 2k+2 – 1 2k+1– 1 (by IH)

  7. eg: Show 22n – 1 is divisible by 3,  n  1 IB: when n = 1, LHS = 22 – 1 = 3 divisible by 3 IS: Assume 22k – 1 is divisible by 3 (22k – 1 = 3m for some integer m), and want to show 22(k+1) – 1 is divisible by 3.  22(k+1) – 1 = 22k+2 – 1 = 22 * 22k – 1 = 22(3m+1) – 1 ( 22k – 1 = 3m 22k = 3m + 1) =12m + 3 = 3(4m + 1) where 4m + 1 is an integer  is divisible by 3

  8. k__ k+1 (by IH)

More Related